The use of the mentoring institute on the example of teaching economic disciplines: patterns and implementation specifics - M. N. Rybina (Вестник университета)
Mentoring in higher education is a necessity and an obligatory process of transferring the experience of teaching staff to young teachers. Statistics show that the younger generation is not eager to devote themselves to teaching, sometimes because they are not aware of all aspects of the profession. The mentoring task in higher education is to involve the younger generation in a unique pedagogical process. The work is complex, requiring from the parties a creative approach and the ability to turn a young specialist in the direction of pedagogy. Everything is important in this process from understanding the financial component to recognizing the social significance of the activity. Mentoring for young teachers, graduate students, masters in teaching economic disciplines, along with the regularities of the process has its own significant features, which arise from the economic reality study specifics, as well as the presence of numerous concepts and theories that interpret this economic reality itself and on the basis of this proposing a certain state economic policy. The issue becomes relevant also because the approaches to the federal state educational standards are being transformed in Russia.